Breast cancer instructs dendritic cells to prime interleukin 13–secreting CD4(+) T cells that facilitate tumor development - Aspord, Caroline (The Rockefeller University Press, 2007)
We previously reported (Bell, D., P. Chomarat, D. Broyles, G. Netto, G.M. Harb, S. Lebecque, J. Valladeau, J. Davoust, K.A. Palucka, and J. Banchereau. 1999. J. Exp. Med. 190: 1417–1426) that breast cancer tumors are infiltrated with mature dendritic cells (DCs), which cluster with CD4(+) T cells. We now show that CD4(+) T cells infiltrating breast cancer tumors secrete type 1 (interferon γ) as well as high levels of type 2 (interleukin [IL] 4 and IL-13) cytokines. Immunofluorescence staining of tissue sections revealed intense IL-13 staining on breast cancer cells. The expression of phosphorylated signal transducer and activator of transcription 6 in breast cancer cells suggests that IL-13 actually delivers signals to cancer cells. To determine the link between breast cancer, DCs, and CD4(+) T cells, we implanted human breast cancer cell lines in nonobese diabetic/LtSz-scid/scid β2 microglobulin–deficient mice engrafted with human CD34(+) hematopoietic progenitor cells and autologous T cells. There, CD4(+) T cells promote early tumor development. This is dependent on DCs and can be partially prevented by administration of IL-13 antagonists. Thus, breast cancer targets DCs to facilitate its development.